Pengaruh Tingkat Inteligansi (IQ) Dan Motivasi Terhadap Indeks Prestasi Komulatif (IPK) Mahasiswa Pengaruh Tinggi Swasta Di Kota Bogor - Supariyani, Emmy; Purba, Jan Horas Veryady (Jurnal Ilmiah Ranggagading (JIR), 2003)
The purpose of this research is, (1) to know the influence of intelligence quotient (IQ) to studentsâ achievement measured by cumulative achievement index. (2) To fathom the influence of motivation towards studentsâ cumulative achievement index, and(3) to apprehend the influence of IQ and motivation simultaneously against studentsâ cumulative achievement index. Parameter coefficient of IQ and respective motivation is 0.0267 and 0.0332. It means of studentsâ IQ at one unit will increase cumulative achievement index at 0.0332. Both are significant at 905 level of confidence (a=0.01). Based on parameter coefficient the two independent variables, that is to say IQ and motivation, could be concluded as well that motivation has more significant influence compare with IQ toward studentsâ achievement. Thereby this research shows that cumulative achievement index does not merely depend on IQ, but extremely determined by studentsâ motivation. The implication of this research is to raise studentsâ motivation and to create conducive climate to prompt students to motivate themselves.